Deteksi Besar Hewan Mamalia Berdasarkan Luas dan Keliling Menggunakan Metode K-MEANS - Mudhi Ulfani Mudhi; Nurul Fadillah (E-Jurnal Universitas Samudra, 2021)
Mammals are a class of vertebrate animals with features such as hair and mammary glands. Mammals are spread almost all over the world and occupy different types of habitats, from the arctic to the equator, from the sea to the land. In this study, a program will be built using the K-means clustering method. The program will classify 60 images from 3 types of mammal images, namely 20 images of bats, 20 images of fish and 20 images of frogs. The cluster results are presented in diagrammatic form. After conducting research on the number of centroids, it can be concluded that the more the number of centroids in each clustering process, the more specific the resulting cluster groups will be. Thus making conclusions on similarities in cluster groups is easier.